Comparative transcriptomics and genomic analyses reveal differential gene expression related to Colletotrichum brevisporum resistance in papaya (Carica papaya L.) - Yang, Min; Zhou, Chenping; Yang, Hu; Kuang, Ruibin; Liu, Kaidong; Huang, Bingxiong; Wei, Yuerong (Frontiers in Plant Science, 2022)
Colletotrichum brevisporum is an important causal pathogen of anthracnose that seriously affects the fruit quality and yield of papaya (Carica papaya L.). Although many genes and biological processes involved in anthracnose resistance have been reported in other species, the molecular mechanisms involved in the response or resistance to anthracnose in post-harvest papaya fruits remain unclear. In this study, we compared transcriptome changes in the post-harvest fruits of the anthracnose-susceptible papaya cultivar Y61 and the anthracnose-resistant cultivar G20 following C. brevisporum inoculation. More differentially expressed genes (DEGs) and differentially expressed long non-coding RNAs (DElnRNAs) were identified in G20 than in Y61, especially at 24 h post-inoculation (hpi), suggesting a prompt activation of defense responses in G20 in the first 24 h after C. brevisporum inoculation. These DEGs were mainly enriched in plant-pathogen interaction, phenylpropanoid biosynthesis/metabolism, and peroxisome and flavonoid biosynthesis pathways in both cultivars. However, in the first 24 hpi, the number of DEGs related to anthracnose resistance was greater in G20 than in Y61, and changes in their expression levels were faster in G20 than in Y61. We also identified a candidate anthracnose-resistant gene cluster, which consisted of 12 genes, 11 in G20 and Y61, in response to C. brevisporum inoculation. Moreover, 529 resistance gene analogs were identified in papaya genome, most of which responded to C. brevisporum inoculation and were genetically different between papaya cultivars and wild-type populations. The total expression dose of the resistance gene analogs may help papaya resist C. brevisporum infection. This study revealed the mechanisms underlying different anthracnose resistance between the anthracnose-resistant and anthracnose-susceptible cultivars based on gene expression, and identified some potential anthracnose resistance-related candidate genes/major regulatory factors. Our findings provided potential targets for developing novel genetic strategies to overcome anthracnose in papaya.